Long Term Efficacy and Safety of Bronchoscopic Thermal Vapor Ablation in Patients with COPD: A Retrospective Study of 50 Patients - Pertzov B; Ben Avraham M; Priel E; Freidkin L; Rosengarten D; Kramer MR (International Journal of COPD)
Barak Pertzov,1– 4 Merav Ben Avraham,1,2 Eldar Priel,3– 5 Lev Freidkin,1,2 Dror Rosengarten,1,2 Mordechai Reuven Kramer1,2 1Pulmonary Division, Rabin Medical Center, Petach Tikva, Israel; 2Sackler Faculty of Medicine, Tel Aviv University, Tel Aviv, Israel; 3Firestone Institute for Respiratory Health, St Joseph’s Healthcare, Hamilton, ON, Canada; 4Department of Medicine, McMaster University, Hamilton, ON, Canada; 5Division of Thoracic Surgery, St. Joseph’s Healthcare, Hamilton, ON, CanadaCorrespondence: Barak Pertzov, Pulmonary Division, Rabin Medical Center, Beilinson Campus, 39 Jabotinski St, Petach Tikva, 4941492, Israel, Tel +972-3-9377221/3, Fax +972-3-9242091, Email pertzovb@gmail.comBackground: Bronchoscopic Thermal Vapor Ablation (BTVA) has demonstrated improvements in FEV1 and quality of life in clinical trials. However, the long-term benefits and overall efficacy of this procedure remain uncertain and are not yet fully established.Methods: We conducted a retrospective observational study of all patients who underwent BTVA at Rabin Medical Center, Israel. The primary outcome was the change in FEV₁ from baseline. Secondary outcomes included other pulmonary function parameters and procedural adverse events.Results: A total of 50 patients were included in the study. The mean FEV1 values at baseline, 6 months, and 12 months post-procedure (n=31) were 0.74± 0.21 L, 0.93± 0.32 L, and 0.85± 0.25 L, respectively (overall P< 0.001; pairwise comparisons: baseline to 6 months, P< 0.001; baseline to 12 months, P=0.016). The mean FVC values at baseline, 6 months, and 12 months post-procedure (n=31) were 1.97± 0.56 L, 2.27± 0.71 L, and 2.14± 0.68 L, respectively (overall P=0.003; pairwise comparisons: baseline to 6 months, P=0.002; baseline to 12 months, P=0.125). Post-procedural complications included pneumonia in 5 patients (11%), of whom 3 developed necrotizing pneumonia and subsequently died, resulting in a 6% post-procedural mortality rate in the entire cohort. Hemoptysis was reported in 1 patient (2%).Conclusion: Bronchoscopic thermal vapor ablation is a minimally invasive bronchoscopic intervention for lung volume reduction. The procedure was associated with significant improvements in FEV₁ at 6 to 12 months and in FVC at 6 months, followed by a gradual decline over 12 to 24 months. Further research is warranted to optimize patient selection, enhance procedural safety, and assess long-term efficacy.Plain Language Summary: COPD is a disease that damages lung tissue. The damaged areas become hyperinflated, compressing healthier parts of the lung and reducing their function. Bronchoscopic Thermal Vapor Ablation (BTVA) is a minimally invasive treatment that uses heated water vapor to target and shrink these damaged areas. During the procedure, a thin tube with a camera (bronchoscope) is inserted into the lungs to deliver vapor directly to diseased regions. The vapor causes controlled injury, leading to shrinkage of the targeted tissue and allowing healthier lung areas to expand and function more effectively. BTVA can be repeated by treating different regions over time, potentially maintaining its benefits.In this study, we evaluated the effectiveness and safety of BTVA in patients with advanced COPD. Lung function improved significantly at 6 and 12 months compared to baseline. Between 12 and 24 months, the benefits gradually declined but remained above baseline.Side effects were primarily pneumonia and temporary coughing up of blood, which resolved in most cases. However, three patients developed severe pneumonia and died, highlighting the need for further research.In conclusion, BTVA improved lung function, but careful selection of treatment areas and energy levels is important to reduce complications and enhance safety.Keywords: COPD, emphysema, BLVR, BTVA, vapor, FEV1, safety